Problem Behavior, Victimization, and Soda Intake in High School Students - Park, Sohyun (Am J Health Behav, 2013)
OBJECTIVE: To examine associations of problem behaviors and victimization with nondiet soda intake among a national sample of 16,188 US high school students. METHODS: We used the 2009 national Youth Risk Behavior Survey. The outcome measure was daily nondiet soda intake. RESULTS: Smoking, having any sex partners, not always wearing a seat belt, being bullied/threatened/injured on school property, and being physically hurt by their boyfriend/girlfriend were significantly associated with daily nondiet soda intake after adjustment for age, sex, race/ethnicity, and weight status. CONCLUSIONS: Our findings suggest a need to examine why nondiet soda intake is associated with these behaviors to understand potential mechanisms.